Blood stream infections in oncology patients at Red Cross War Memorial Children's Hospital, Cape Town - Mvalo, Tisungane Knox Titus (Department of Paediatrics and Child Health, 2018)
Background: Infections cause significant morbidity and mortality in children with cancer, which may be related to the cancer or treatment received. There is paucity of data on the epidemiology of bloodstream infection (BSI) in sub-Saharan Africa. To address this knowledge gap, the present study was conducted at Red Cross War Memorial Children's Hospital (RCWMCH) in Cape Town, South Africa. Methods: Structured literature review: From 1 April 2016 to 31 May 2016 a PubMed search was undertaken on BSI in Paediatric Oncology. The search string used was (bacteraemia OR blood stream infection) AND (paediatric OR pediatric) AND (oncology). Studies that did not describe infection patterns, risk factors for infection, morbidity/mortality, articles not in English and those exclusively describing neonatal or ICU patients were excluded from full review. Retrospective cohort study: A retrospective cohort study was conducted at the haematology-oncology unit of RCWMCH. All positive blood cultures from RCWMCH oncology patients taken between 1 January 2012 and 31 December 2014 were retrieved to identify patients who had BSI. Results: Structured literature review: 508 abstracts / articles were initially retrieved and screened. 478 studies were excluded as per the literature review exclusion criteria. Thus, 30 articles were included in full analysis, 17 retrospective studies, 4 prospective multicentre studies, 6 prospective single centre studies, 2 systematic reviews and 1 case report. All were observational studies. This literature review showed that BSI is a frequent and important cause of morbidity and mortality in paediatric oncology. Gram-positive bacteria was noted to be the leading type of pathogen causing BSI. Increased risk of BSI may be from the cancer itself, chemotherapy, hospitalisation, central venous catheter insertion, and oncology patients were at risk of multi-drug resistant infection. Research gaps noted included paucity of studies from Sub-Saharan Africa, limited analysis of the antimicrobial susceptibility of causative microorganisms and limited description of fungal BSI in oncology patients. Retrospective cohort study: From 436 positive blood culture results, 150 BSI episodes were identified amongst 89 patients; 49.1% of the culture isolates were Gram-positive bacteria, 41.6 were Gram-negative bacteria and 9.3% were fungal. Coagulase Negative Staphylococcus and Viridans Group Streptococcus were the most common Gram-positive isolates, and Escherichia coli and Klebsiella species the commonest Gram-negative isolates. The majority of BSI episodes occurred in patients with haematological malignancies (74%), in the presence of severe neutropaenia (76.4%) and whilst on or following chemotherapy (88%). Complications occurred in 14% of the BSI episodes. Fungal infections had the highest prevalence of complications (21.4%). Three children died during BSI as a result of multidrug resistant isolates, giving a case-fatality rate of 2%. Conclusion: The findings of our cohort study show that BSI are mainly caused by Gram-positive bacteria and associated with a low case-fatality rate. The results of this study are consistent with worldwide experience of BSI in paediatric oncology patients. This study provides an understanding of the spectrum of organisms causing BSI and the outcome of BSI in a sub-Saharan African context.